2020
DOI: 10.21608/jpp.2020.110555
|View full text |Cite
|
Sign up to set email alerts
|

Generation Mean Analysis for Three Bread Wheat Crosses under Normal and Water Stress Treatments

Abstract: The objective of this study was to identify tolerant and susceptible genotypes of bread wheat under different irrigation treatments and determine the type of gene action and some genetic parameters in three bread wheat crosses; (Line 1 × Line 2), (Line1 × Giza 171) and (Misr 2 × Line 3) under normal irrigation and water stress treatments. Genetic materials included six populations (P1, P2, F1, F2, BC1 and BC2) for each cross. Positive and high significant values for heterotic effects relative to the mid-parent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(14 citation statements)
references
References 8 publications
10
4
0
Order By: Relevance
“…Means of the six populations significantly differed in most studied characters, indicating to genetic variability for statistical-genetic analyses. Similar results were detected by Elmassry and El-Nahas (2018) and Sharshar and Genedy (2020).…”
Section: Resultssupporting
confidence: 90%
See 2 more Smart Citations
“…Means of the six populations significantly differed in most studied characters, indicating to genetic variability for statistical-genetic analyses. Similar results were detected by Elmassry and El-Nahas (2018) and Sharshar and Genedy (2020).…”
Section: Resultssupporting
confidence: 90%
“…All the studied crosses showed highly significant mean effects (m) for all traits, indicating quantitative inheritance. These findings are in accordance with Elmassry and El-Nahas (2018) and Sharshar and Genedy (2020).…”
Section: Gene Actionsupporting
confidence: 93%
See 1 more Smart Citation
“…of kernels/spike in cross II. (Sharshar and Genedy, 2020), found that significant positive heterosis and heterobeltiosis were obtained for No. of spikes/plant, 100-kernel weight and grain yield/plant.…”
Section: Heterosis and Heterobeltiosismentioning
confidence: 97%
“…Also, for better parent heterosis, significant, highly significant, as well as a positive heterotic effect was detected for all the examined traits. Sharshar and Genedy (2020) reported that significant positive heterosis relative to better and mid-parent was obtained for yield components as well as grain yield.…”
Section: Heterosis Estimatesmentioning
confidence: 99%